Silenced and sidelined how women leaders find their voices and break barriers - Arnold, Carrie Lynn, 1970- (Rowman & Littlefield, 2020)
"Women are told to speak up, develop confidence, leverage their strengths, polish their interpersonal skills, widen their competencies, and sit at the table. Rarely are they able to examine the relationships or systems that may silence them or keep them from essential professional development that scholars and business authors across the globe argue is necessary. The examination of silencing is a pre-requisite to effective leadership. We have to name what has been our experience before we can successfully shift it to something else. We must understand where we have been before we can appreciate where we need to go. For decades, women have fought, clung, climbed, pilgrimed, aspired, and at times, clawed to higher and higher levels of leadership. It can be isolating for a woman to realize she still feels silenced after landing in that sought-after executive role. It is also impossible to avoid encounters, organizational cultures, or the self that attempts to silence. This is no longer just about competency or confidence. It is about understanding the complex factors that are deeply embedded in relationships between men and women; amongst women; and within the dynamics of systems and self. Regardless of your gender or whether you are an emerging leader or a CEO of a large corporation, the silencing virus is capable of infecting everyone. This book explores what it means to feel silenced and gives words to the phenomenon so that leaders can begin different types of conversations about voice and leadership. There are no shortcuts or simple, easy steps; the call to leadership is a call for courage. The calling requires the ability to communicate with a voice that carries currency-one, people will not just hear, but follow. Given the complexity of our world and the challenges society faces, we can no longer afford leaders with silenced voices"--